(untitled) (Fiep Bulletin - online, 2014)
The autonomic nervous system regulates the internal functions of the human body, presenting hormonal responses associated with their condition. In this sense, the practice of motor activity seems to result in changes that provide system homeostasis imbalances in the individual, especially in high levels of performance. However, although it may be relevant to the control of variables related to the autonomic behavior of the athlete in order to verify the actual organic internal imbalances that training can provide, there are few studies that show the responses resulting from this effort. In the present study, the levels of activity of the sympathetic and parasympathetic nervous of high performance athletes practicing athletics were observed by analysis of heart rate variability (HRV). The test results of 03 athletes showed high level of autonomic balance in pre-training test and sympathetic prevalence in immediate post workout. The test showed a prevalence of 01 athlete sympathetic pre-workout and depression of parasympathetic receptors in the immediate post-workout. These findings confirm what is described in literature, showing that HRV analysis through software Nerve-Express consists of a new method, effective and non-invasive to the identification of problems related to the autonomic nervous system, and it can be used as test screening to assess changes in the SNA prematurely.